Pengaruh Inflasi Dan Pengangguran Terhadap Pertumbuhan Ekonomi Di Provinsi Bali - Yogi Adetya Kurniawan; Ronny Malavia Mardani; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of inflation and unemployment on economic growth in the city/regency of Bali province 2014-2020. The sample used is all cities/districts of the province of Bali. Data retrieval using the method of documentation. The test data used are simultaneous hypothesis testing (f), coefficient of determination (R2), and partial hypothesis testing (t). The results of this study indicate that the independent variable simultaneously has a significant effect on the dependent variable. Based on the results of the coefficient of determination test, the value of R2 Square is 35.7% while the remaining 64.3% is influenced by other variables not included in this study. Based on the partial test results, the inflation variable (sig = 0.000) has a significant effect on economic growth while unemployment (sig = 0.077) has no effect on economic growth. Keywords: Inflation, Unemployment and Economic Growth